2018
DOI: 10.1007/s13239-018-0342-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of a Self-Powered Fontan Circulation

Abstract: Children born with anatomic or functional "single ventricle" must progress through two or more major operations to sustain life. This management sequence culminates in the total cavopulmonary connection, or "Fontan" operation. A consequence of the "Fontan circulation", however, is elevated central venous pressure and inadequate ventricular preload, which contribute to continued morbidity. We propose a solution to these problems by increasing pulmonary blood flow using an "injection jet" (IJS) in which the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…Lack of pulsatile flow will result in elevation of pulmonary artery pressure, pulmonary vascular resistance 26,27 , and decreased endothelial-dependent vasorelaxation response of the pulmonary arteries 25 , which has a pernicious effect on Fontan circulation. Although the mass flow rate of RPA was significantly increased in this study, pressure of the venae cavae would not reach the criterion of pulmonary hypertension even if pulmonary vascular resistance was relatively high 16,17 .…”
Section: Discussionmentioning
confidence: 61%
“…Lack of pulsatile flow will result in elevation of pulmonary artery pressure, pulmonary vascular resistance 26,27 , and decreased endothelial-dependent vasorelaxation response of the pulmonary arteries 25 , which has a pernicious effect on Fontan circulation. Although the mass flow rate of RPA was significantly increased in this study, pressure of the venae cavae would not reach the criterion of pulmonary hypertension even if pulmonary vascular resistance was relatively high 16,17 .…”
Section: Discussionmentioning
confidence: 61%
“…In the coupling scheme, the 0D LPMs with resistance elements were coupled with the 3D model at the outlet boundaries, including the outlets of descending aorta (DAo), BA, LCCA and LSA. A "tight coupling" algorithm [29][30][31] was used to transfer the data at the coupling interfaces. At the beginning of the coupling, an initial pressure is applied as the initial condition.…”
Section: ( • ∇ ) = −∇ + ∇mentioning
confidence: 99%
“…TCPC allows to support an acceptable level of pulmonary circulation with reduction of the patients’ morbidity and mortality . At the same time, there is a high risk of the cardiovascular system to fail due to various reasons such as ventricular dysfunction, elevated pulmonary vascular impedance, inadequate preload to the ventricle, increased neurohumoral activation, and elevated systemic venous pressure . In order to increase the patients’ survival rate and the quality of their life, along with different TCPC connections oriented to improve blood hemodynamics, mechanical circulatory support (MCS) is applied as another auspicious treatment option …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that 3D and 4D blood flow data received from computational fluid dynamics (CFD) and magnetic resonance imaging can be used for measuring the adverse energetics . Whereas multi‐scale modeling can be used for the simulation of the hemodynamic effects of the Fontan circulation . In theory, an optimal TCPC connection should decrease the loading level of a single ventricle and extend the life of the Fontan patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation